Predicting the Multisensory Consequences of One’s Own Action: BOLD Suppression in Auditory and Visual Cortices - Straube, Benjamin (PLoS One, 2017)
Predictive mechanisms are essential to successfully interact with the environment and to compensate for delays in the transmission of neural signals. However, whether and how we predict multisensory action outcomes remains largely unknown. Here we investigated the existence of multisensory predictive mechanisms in a context where actions have outcomes in different modalities. During fMRI data acquisition auditory, visual and auditory-visual stimuli were presented in active and passive conditions. In the active condition, a self-initiated button press elicited the stimuli with variable short delays (0-417ms) between action and outcome, and participants had to detect the presence of a delay for auditory or visual outcome (task modality). In the passive condition, stimuli appeared automatically, and participants had to detect the number of stimulus modalities (unimodal/bimodal). For action consequences compared to identical but unpredictable control stimuli we observed suppression of the blood oxygen level depended (BOLD) response in a broad network including bilateral auditory and visual cortices. This effect was independent of task modality or stimulus modality and strongest for trials where no delay was detected (undetected<detected). In bimodal vs. unimodal conditions we found activation differences in the left cerebellum for detected vs. undetected trials and an increased cerebellar-sensory cortex connectivity. Thus, action-related predictive mechanisms lead to BOLD suppression in multiple sensory brain regions. These findings support the hypothesis of multisensory predictive mechanisms, which are probably conducted in the left cerebellum.